The effectiveness of distance e-learning in light of the Corona pandemic and its obstacles from the point of view of teachers of the northeastern Badia in Jordan - Saleem, Niveen Abed–Alhaleem (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the effectiveness of e-learning and distance learning in light of the spread of the Corona virus pandemic from the point of view of teachers in the northeastern Badia in Jordan. And a teacher in the North Eastern Badia Education Directorate who taught during the period of the spread of the Corona virus with the e-learning system.The results of the study revealed that the study sample’s evaluation of the effectiveness of e-learning and distance learning in light of the spread of the Corona virus pandemic, from their point of view, the field of student interaction in the use of distance e-learning obtained a total average (2.47 out of 5), i.e. a (weak) degree The results also showed that there were statistically significant differences at the significance level (α ≥ 0.05) between the sample estimates according to the gender variable and in favor of males; While there were no significant differences depending on the two variables (the educational qualification - the type of study) and based on the results, the researcher recommended holding training courses in the field of e-learning for both teachers and students and to help get rid of all the obstacles that prevent benefiting from the followed e-learning system, and the need to integrate education Face and e-learning in educational institutions in the future.
Keywords: e-learning; distance learning; corona virus; northeastern Badia region